(untitled) (Eurasian Medical Research Periodical, 2022)
Failure of spinal anesthesia for a cesarean section (C-Section) may have both maternal and neonatal deleterious sequel, Contrivances of spinal anesthesia failure in addition to the “approach to a failed block” have been discussed in this article.